(untitled) (Research, Society and Development, 2020)
The search for small fruits, for consumers, has increased in recent times due to the great research on bioactive, which brings benefits associated with the maintenance and well-being of health. With this, agro-industries have also focused on expanding the consumer market for fruit pulp. Thus, blackberry and blueberry crops gain space among other species, from the small fruits consumed in Brazil, attract the attention of consumers, fruit processors, marketing agents and, consequently, producers on a family, medium and large scale. The objective of this study was to evaluate the antioxidant activity of fresh pulp, diluted pulp and freeze-dried blackberry pulp cv. Tupy and blueberry pulp cv. Powderblue. Blackberries (Rubus fruticosus) from the cultivar cv. Tupy and blueberries (Vaccinium ashei Reade) from cv. Powderblue, both grown in the city of Morro Redondo-RS, were used. The previously frozen fruits (-18°C) were kept at room temperature until thawing, and then crushed in a blender and sieved to obtain the pulp, which were diluted with mineral water in the proportions of 50% and 75% w/v (pulp: water). The fruit was also stored and removed from the ultrafreezer (-80°C) and immediately freeze-dried, after which it was stored in polyethylene containers under freezing (-20±2°C) until the time of analysis. The antioxidant activity was determined following the method described by Brand-Willians. Therefore, it was found that the pulp -in natura of blueberry cv. Powderblue presents a greater antioxidant capacity than the blackberry cv. Tupy.